Evidence of the plain ware of Paullus from Lezoux in Pannonia - Kuzmová, Klára (Rei Cretariae Romanae Fautorum Acta, 2017)
The impulse for choosing the topic of this contribution were fragments of two conical cups Drag. 33 stamped by Paullus from Lezoux, which had been found in the earth-and-timber fort at Iža (Slovakia), a site that lies on the left bank of the Danube and which acted as a bridgehead of the legionary fortress Brigetio (Komárom/Szőny, Hungary) on the northern frontier of Pannonia. These cup fragments are significant primarily from the chronological point of view because they come from the earliest building phase of the auxiliary fort, from a context which dates back to the final stage of the Marcomannic wars, i.e. to the period between the years 175–179 AD. They were uncovered in the rooms of two neighbouring barracks made of unfired bricks, which were situated near the assumed south-eastern corner of the fort. On the basis of their well-datable context, correlated with one of the interactions between the Romans and the Germanic tribes of the Quadi during the Marcomannic wars, the cups may help specify the dating of their parallels, and advance our knowledge about the distribution and use of this ware in Pannonia in the late 170s.